Sistem dinamis Pendekatan Sistem Dinamis pada Pengendalian Hama dan Adaptasi Teknologi Guna Meningkatkan Profitabilitas - Akbar, Daffa Athillah; Murnawan, Hery; Wati, Putu Eka Dewi Kurnia; Widiasih, Wiwin (Universitas Muhammadiyah Sorong, 2025)
Desa Sentul is a village where 74% of its total area is agricultural land primarily used for rice cultivation, This research aims to analyze the factors influencing food security and farmer profitability in Sentul Village, Jombang Regency, and to develop a system dynamics model to support agricultural sustainability. Using a Triple Bottom Line approach with SMART PLS, the analysis results show that age, technology adoption, pest attacks, fertilizer use, and soil pH significantly impact productivity and food security. The system dynamics model developed with STELLA illustrates the relationships between these factors and highlights the importance of proper fertilizer and pest management. Three simulation scenarios were tested to increase farmer productivity and profit, with Scenario 3 (a combination of technological and organic approaches) showing the most optimal results, increasing rice productivity by up to 14%, reducing operational costs by up to 21%, and increasing profit by Rp2,507,146,451. The study also includes risk analysis and mitigation strategies for scenario, which are expected to reduce challenges and enhance agricultural sustainability in Sentul Village.